OPTIMALISASI MITIGASI DAN PENEGAKAN HUKUM HAK CIPTA TERKAIT PEMBAJAKAN SCANLATION KOMIK PADA WEBSITE ILLEGAL - Alberto Eka Sutisna (Universitas Islam Malang, 2022)
Copyright piracy is a problem in the growth of the creative economy, especially the comic book industry. Where the use of technology provides changes to creations that previously only existed in physical form, and can now be converted into digital form. This writing is intended to complement the treasury of studies related to copyright law piracy which offers a concept of optimization and law enforcement in redressing the problem of comic scanlation piracy in Indonesia. The research method used by the author in this scientific paper is normative juridical research which is complemented by interviews and built with the framework of law enforcement theory by Lawrence M. Friedman. Scanlation is defined as an act of scanning and translation which refers to the distribution of comics by reproducing illegal digital comics to be copied and distributed. Therefore, there is a need for laws and regulations that regulate the form of protection for comics in the digital space and the active role of copyright law enforcement agencies, the private sector and the general public to take responsibility for this scanlation piracy act.